A method for preparing small diameter nanocarbon fibers by floating catalytic chemical vapor deposition

Through the combination of the solid-liquid dual-catalyst system and the catalyst inhibitor, the problem of difficulty in controlling the catalyst proportion is solved, and the preparation of high-yield and high-purity small-diameter nanocarbon fibers is achieved, which improves the preparation efficiency and quality of nanocarbon fibers.

CN115852530BActive Publication Date: 2024-12-20HENAN KLEWAY NANO CARBON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211450246.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-19
Publication Date
2024-12-20
Estimated Expiration
2042-11-19

AI Technical Summary

Technical Problem

In the preparation of small diameter nanocarbon fibers, the catalyst ratio is difficult to regulate, resulting in low yield and uncontrollable product. Especially in chemical vapor deposition method, the solubility of the catalyst in liquid carbon sources is limited, which affects the temperature field in the furnace and Uniformity of ingredients.

Method used

Using a solid-liquid dual-catalyst system, combined with a catalyst inhibitor, the catalyst is mixed evenly through ultrasonic or mechanical stirring, and nanocatalyst clusters are formed using high temperatures, and vapor deposition is carried out in a synthesis furnace to control the catalyst components, and coordinate preheating carbon source and carrier. gas realizes batch preparation of small-diameter nanocarbon fibers.

Benefits of technology

The preparation of small-diameter nanocarbon fibers with high yield and high purity has been achieved, which solves the problems of difficulty in controlling the proportion of catalysts and uncontrollable products, and improves the preparation efficiency and quality of nanocarbon fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115852530B_ABST
    Figure CN115852530B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of carbon fiber, and specifically relates to a method for preparing small-diameter nano-carbon fiber by floating catalytic chemical vapor deposition. The method comprises: introducing material catalyst steam, promoter steam, carbon source steam, and preheated carrier gas into a synthesis furnace, synthesizing carbon fiber at 800-1400°C, and then purifying and crushing to obtain nano-carbon fiber; the catalyst is an organic catalyst, and the organic catalyst system comprises a liquid catalyst first component and a solid catalyst second component, and the solid catalyst second component is dissolved in the catalyst first component; an inhibitor is added to the material to prevent the catalyst from agglomerating. The method can realize the batch preparation of small-diameter nano-carbon fiber, and realize the increase of output, and the prepared nano-carbon fiber has high output and good purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber, and in particular relates to a method for preparing small-diameter nano carbon fiber by floating catalytic chemical vapor deposition. Background Art

[0002] There are two main methods for preparing nano carbon fiber at present: one is to adopt electrostatic spinning method to make, polyacrylonitrile fiber is subjected to oxidation carbonization graphitization treatment to obtain, the length of fiber preparation can reach millimeter level, but the strength of fiber is poor, and there is obstacle when preparing <50nm fine fiber at the same time; the second is nano carbon fiber prepared by chemical vapor deposition method, adopts organic transition metal as catalyst, takes hydrocarbon as carbon source, and carbon source is mostly liquid, and this method can prepare nano carbon fiber of small diameter. Generally, organic transition metal catalyst (ferrocene, nickelocene, cobaltocene) catalyst is dissolved in carbon source (benzene, toluene, ethanol, n-hexane), carbon source and catalyst mixed solution are passed into synthesis furnace together, but the operability of each component is poor, because the solubility of catalyst in liquid carbon source is limited, especially the ratio of catalyst is not well regulated, catalyst ratio adjustment range is limited, can not further increase the amount of catalyst, thus output can not be improved. At the same time, the temperature field inside the furnace and the uniformity of composition are affected, resulting in uncontrollable product.

[0003] The invention patent application with publication number CN109437157A adopts a method of mixing the catalyst and the carbon source for feeding, the catalyst ratio is adjusted between 3 and 8 wt%, the maximum preparation amount is 0.32 g / h, and the output is relatively low.

[0004] Therefore, how to prepare high-concentration small-particle catalysts is a key factor limiting production. Summary of the invention

[0005] The present invention provides a method for preparing nano-carbon fibers with controllable and uniform diameters. The method can realize batch preparation of small-diameter nano-carbon fibers and increase the yield. The prepared nano-carbon fibers have high yield and good purity.

[0006] The present invention provides a method for preparing small-diameter carbon nanofibers by floating catalytic chemical vapor deposition, which is suitable for large-scale quantitative production. The technical solution of the present invention is:

[0007] The material catalyst steam, promoter steam, preheated carbon source and preheated carrier gas are introduced into a synthesis furnace to synthesize carbon fibers at 800-1400°C. After purification and crushing, the obtained nano-carbon fibers have a diameter of 1-200nm and a length of 2-200μm.

[0008] The catalyst is an organic catalyst, and the organic catalyst system is a solid-liquid dual catalyst system, which comprises a liquid catalyst first component and a solid catalyst second component, and the solid catalyst second component is dissolved in the first component.

[0009] When the catalyst particles are exposed to high temperatures, the nano-catalyst particles aggregate into clusters. Therefore, a catalyst inhibitor can be added to the material to control the growth of the catalyst and thus control the amount of the catalyst component.

[0010] The preparation process of small diameter carbon nanofibers is as follows:

[0011] (1) Catalyst, promoter, and carbon source vaporization

[0012] First, the first component of the catalyst and the second component of the catalyst are uniformly mixed by ultrasonic or mechanical stirring, and then the catalyst and the promoter are vaporized separately; or the promoter and the catalyst are mixed and vaporized. The purpose of vaporization is to prepare a high-concentration small-particle catalyst.

[0013] Among them, the first component of the catalyst is ethylferrocene, pentacarbonyl iron, tert-butylferrocene, 2,2-bis(ethylferrocenyl)propane or octylferrocene; the second component of the catalyst is ferrocene, nickelocene, cobaltocene, molybdenum acetate, molybdenum acetonate acetate, tungsten hexachloride, molybdenum ethoxide or copper acetoacetate; the ratio of the first component of the catalyst to the second component of the catalyst is (1-10):1.

[0014] The accelerator is a sulfur- and phosphorus-containing substance, and further is one or more of thiophene, mercaptan, sulfur powder, carbon disulfide, hydrogen sulfide, and phosphoric acid.

[0015] The carbon source needs to be preheated separately, and the temperature of the preheated carbon source steam is 70-500°C. The purpose of this is to eliminate the impact on the temperature field of the synthesis furnace and achieve better product uniformity.

[0016] The carbon source is one or more of methane, ethylene, acetylene, ethanol, acetone, toluene, xylene, benzene, and n-hexane; the choice of the carbon source is determined according to the synthesized product, and the cracking temperatures of different carbon sources are different. The cracking temperatures of methane, toluene, xylene, and benzene are high, while the cracking temperatures of ethylene and acetylene are low. By mixing different carbon sources, the purpose of controlling the catalyst to start growing at different sizes is achieved, thereby realizing the control of the diameter and length of nano-carbon fibers.

[0017] (2) Carrier gas preheating

[0018] The carrier gas is one or more of hydrogen, nitrogen and argon. A preheater is used to preheat the carrier gas at a preheating temperature of 100 to 600°C.

[0019] (3) Materials are fed into the synthesis furnace

[0020] The materials catalyst, promoter, carbon source and carrier gas can be introduced into the synthesis furnace separately or in combination. If they are introduced into the synthesis furnace after being combined, they need to be forcibly mixed by a mixer after being combined, and then introduced into the synthesis furnace after being mixed. Specifically, the following methods can be adopted:

[0021] ① The catalyst steam, promoter steam, carbon source steam and preheated carrier gas are mixed evenly through a mixer and then introduced into the synthesis furnace;

[0022] ② The catalyst steam, promoter steam and carbon source steam are mixed through a mixer and introduced into the synthesis furnace, and the preheated carrier gas is introduced into the synthesis furnace alone;

[0023] ③ The carbon source steam is introduced into the synthesis furnace alone, and the catalyst steam, promoter steam and preheated carrier gas are mixed and introduced into the synthesis furnace. The flow rate of the carbon source, promoter, catalyst and carrier gas mixture is 10-100 m / s, and the time in the synthesis furnace is 30s-10min. The flow rate is mainly adjusted to adjust the time of the product in the synthesis furnace to achieve the purpose of adjusting the catalyst size and adjusting the product diameter and length.

[0024] The inhibitor can be added to any material component separately. The purpose of adding the inhibitor is to prevent the agglomeration of the catalyst, which is more conducive to the synthesis of fine-diameter nano-carbon fibers. The inhibitor is one or more of polyvinyl pyrrolidone, orthosilicate, silicon dioxide, polyvinyl alcohol, polyethylene glycol, and polyacrylamide.

[0025] A small amount of water may be added to the above materials according to the situation. A small amount of water is beneficial to the increase of product yield and the removal of amorphous carbon.

[0026] Among the above materials, by mass, the amount of catalyst is 2-30% of the carbon source, the amount of promoter is 10-50% of the catalyst, and the amount of inhibitor is 10-50% of the catalyst.

[0027] (3) Synthesis of carbon nanofibers

[0028] The materials are synthesized into small-diameter nano-carbon fibers at 800-1400°C in a high-temperature synthesis furnace, and then collected through a gas-solid separation device. During the production process, the synthesis of nano-carbon fibers will undergo a gas-liquid-solid process. In the gas phase process, the catalyst will become liquid. The liquid catalyst is easy to adhere to the wall of the furnace, so the furnace wall should be cleaned regularly to allow the reaction to continue.

[0029] (4) The prepared nano-carbon fiber powder is graphitized or pickled to remove metal impurities. The graphitization allows the carbon atoms to rearrange. The graphitization is carried out by internal string, Acheson, induction or plasma. The graphitization temperature is 2000-3200°C.

[0030] (5) The purified carbon nanofibers are then crushed using a jet mill, a mechanical crusher, or the like.

[0031] The beneficial effects of the present invention are:

[0032] The present invention adopts a solid-liquid dual catalyst system and adds a catalyst inhibitor to the material. The catalyst growth is controlled by the catalyst inhibitor, and then the amount of the catalyst component is controlled, thereby realizing batch preparation of small-diameter nano-carbon fibers and increasing the output. The prepared nano-carbon fibers have high output and good purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope (SEM) photograph of the nano-carbon fiber prepared in Example 2.

[0034] Figure 2 This is a transmission electron microscope TEM photograph of the nano-carbon fiber prepared in Example 2.

[0035] Figure 3 This is the Raman spectrum test result of the nano-carbon fiber prepared in Example 2.

[0036] Figure 4 This is a scanning electron microscope (SEM) photograph of the nano-carbon fiber prepared in Example 3.

[0037] Figure 5 This is a transmission electron microscope TEM photograph of the nano-carbon fiber prepared in Example 3.

[0038] Figure 6 This is the Raman spectrum test result of the nano-carbon fiber prepared in Example 3.

[0039] Figure 7 It is a schematic diagram of the structure of a synthesis furnace, in which 1 is a carbon source feed pipe, 2 is a catalyst feed pipe, 3 is a promoter feed pipe, 4 is a carrier gas inlet pipe, 5 is a mixer, 6 is an ultrasonic atomization device, 7 is a cleaning mechanism, 8 is a synthesis furnace body, 9 is a gas-solid separator, and 10 is a preheater. DETAILED DESCRIPTION

[0040] The present invention is described in more detail below through specific implementation modes to facilitate understanding of the technical solution of the present invention, but is not intended to limit the protection scope of the present invention.

[0041] Example 1

[0042] like Figure 7 As shown, the vertical tubular synthesis furnace of this embodiment includes a synthesis furnace body 8, and a material feed pipe and a carrier gas feed pipe 4 are arranged on the top of the synthesis furnace body 8. The material feed pipe includes a carbon source feed pipe 1, a catalyst feed pipe 2 and a promoter feed pipe 3. The carbon source feed pipe 1, the catalyst feed pipe 2 and the promoter feed pipe 3 are combined and enter the synthesis furnace body 8 through a mixer. A preheater 10 is arranged on the carbon source feed pipe 1, the catalyst feed pipe 2, the promoter feed pipe 3 and the carrier gas feed pipe 4. An ultrasonic atomization device 6 is arranged at the end of the material feed pipe to vaporize and spray the preheated material. A cleaning mechanism 7 is arranged on the inner wall of the synthesis furnace body 8, and a gas-solid separator 9 is arranged below the synthesis furnace body 8.

[0043] When using the synthesis furnace, the preheated catalyst, preheated accelerator and preheated carbon source are mixed by a mixer, atomized by an atomizing device and then introduced into the synthesis furnace, and the preheated carrier gas is introduced into the synthesis furnace alone.

[0044] Example 2

[0045] This embodiment uses a vertical tubular synthesis furnace for synthesis. The vertical tubular synthesis furnace of this embodiment is basically the same as that of Example 1, except that the carbon source feed pipe, catalyst feed pipe, promoter feed pipe and carrier gas feed pipe of this example are connected to a mixer after merging, and the outlet of the mixer is connected to the synthesis furnace body through a feed main pipe, and an ultrasonic atomization device is provided at the end of the feed main pipe.

[0046] The heating zone of the vertical tubular synthesis furnace is 1m long and the furnace tube diameter is 6cm. The liquid first component of the catalyst ethylferrocene and the solid second component of the catalyst ferrocene and the inhibitor polyvinylpyrrolidone are configured in a ratio of 10:1:2, mixed evenly by ultrasonic stirring, and then preheated and vaporized at 400°C.

[0047] The carbon source is xylene, which is preheated to 350°C. The promoter is thiophene, which is preheated and vaporized at 350°C. The carrier gas is hydrogen, with a preheating temperature of 350°C and a hydrogen flow rate of 1m 3 / h.

[0048] The preheated catalyst mixture steam, the preheated promoter steam, the preheated carbon source steam and the preheated H 2, passed into a mixer for mixing, then atomized by an ultrasonic atomizer, and then passed into a 1200℃ high-temperature synthesis furnace. When feeding the materials, an injection pump is used to control the feed rate of the catalyst mixture to 3mL / h, an injection pump is used to control the feed rate of the carbon source to 100mL / h, and an injection pump is used to control the feed rate of the promoter to 1mL / h. Then it is collected through a collection bin, and the furnace wall is cleaned using a cleaning mechanism on the inner wall of the synthesis furnace. The collected product is 2g / h.

[0049] The prepared powder is acid-washed and purified, and then the purified nano-carbon fiber is crushed. The equipment used for crushing is a jet mill, etc. The particle size after crushing is D50 is 3.2μm, D90 is 8.9μm, and Dmax is 18.9μm. The internal agglomeration phenomenon is eliminated by mechanical crushing to achieve a better dispersion effect. The average fiber diameter is tested to be 1.7nm.

[0050] The SEM, TEM and Raman spectra of the generated nano carbon fiber powder were tested. The diameter of the product was characterized by SEM and TEM, and the IG / ID ratio of the Raman spectrum was used to characterize the degree of defect of the product. The test results are shown in Figure 1 , Figure 2 , Figure 3 .

[0051] Example 3

[0052] This embodiment uses a vertical tubular synthesis furnace for synthesis, and the vertical tubular synthesis furnace is the same as that of Embodiment 2.

[0053] The heating zone of the vertical tubular synthesis furnace is 1 m long and the furnace tube diameter is 6 cm. The liquid first component of the catalyst ethylferrocene, the solid second component of the catalyst ferrocene and the inhibitor ethyl orthosilicate are configured in a ratio of 10:1:2, mixed evenly by ultrasonic stirring, and then preheated and vaporized at 400°C.

[0054] The carbon source was ethanol, which was preheated to 350°C. The promoter was thiophene, which was preheated and vaporized at 350°C. The carrier gas was hydrogen, with a preheating temperature of 350°C and a hydrogen flow rate of 1 m 3 / h.

[0055] The preheated catalyst mixture steam, the preheated promoter steam, the preheated carbon source steam and the preheated H 2, passed into a mixer for mixing, then atomized by an ultrasonic atomizer, and then passed into a 1200℃ high-temperature synthesis furnace. When feeding the materials, an injection pump was used to control the feed rate of the catalyst mixture to 3mL / h, an injection pump was used to control the feed rate of the carbon source to 200mL / h, and an injection pump was used to control the feed rate of the promoter to 1mL / h. Then the materials were collected through a collection bin, and the furnace wall was cleaned by a cleaning mechanism. The collected product was 25g / h.

[0056] The prepared powder was graphitized by the Acheson graphitization method. The graphitization temperature was 2800°C and the temperature was maintained for 120 minutes.

[0057] The purified graphitized nanocarbon fibers were crushed using a jet mill. The particle size after crushing was controlled at 3.5 μm for D50, 9.5 μm for D90, and 18.7 μm for Dmax. The internal agglomeration was eliminated through mechanical crushing to achieve a better dispersion effect. The average fiber diameter was tested to be 75 nm.

[0058] The SEM, TEM and Raman spectra of the generated nanocarbon fiber powder were tested. The test results are shown in Figure 4 , Figure 5 , Figure 6 .

[0059] Control group 1 is basically the same as Example 2, except that no inhibitor is used in control group 1. The characterization of the prepared product is shown in Table 1.

[0060] Example 4 is basically the same as Example 2, except that the inhibitor used in Example 4 is ethyl orthosilicate. The characterization of the prepared product is shown in Table 1.

[0061] Example 5 is basically the same as Example 4, except that Example 5 uses ethanol as the carbon source. The characterization of the prepared product is shown in Table 1.

[0062] Example 6 is basically the same as Example 3, except that Example 6 uses cobaltocene as the second component of the catalyst. The characterization of the prepared product is shown in Table 1.

[0063] Example 7 is basically the same as Example 2, except that the catalyst injection rate of Example 7 is 5 mL / h. The characterization of the prepared product is shown in Table 1.

[0064] Example 8 is basically the same as Example 4, except that the accelerator injection rate of Example 8 is 3 mL / h. The characterization of the prepared product is shown in Table 1.

[0065] Table 1 Product characteristics of different embodiments

[0066]

[0067]

[0068] The embodiments described above are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features and principles described in the patent scope of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for preparing small-diameter carbon nanofibers by floating catalytic chemical vapor deposition, characterized in that: Includes the following: The material catalyst steam, promoter steam, carbon source steam and preheated carrier gas are introduced into a synthesis furnace to synthesize carbon fibers at 800-1400°C, and then purified and crushed to obtain nano-carbon fibers; The catalyst is an organic catalyst, which includes a liquid first catalyst component and a solid second catalyst component, wherein the solid second catalyst component is dissolved in the first catalyst component; an inhibitor for preventing the catalyst from agglomerating is added to the material; the first catalyst component is ethylferrocene, pentacarbonyl iron, tert-butylferrocene, 2,2-bis(ethylferrocenyl)propane or octylferrocene; the second catalyst component is ferrocene, nickelocene, cobaltocene, molybdenum acetate, molybdenum acetonate acetate, tungsten hexachloride, molybdenum ethoxide or copper acetoacetate; the ratio of the first catalyst component to the second catalyst component is (1-10):1; The inhibitor is one or more of polyvinyl pyrrolidone, orthosilicate, silicon dioxide, polyvinyl alcohol, polyethylene glycol, and polyacrylamide; The accelerator is a substance containing sulfur and phosphorus.

2. The method for preparing small-diameter carbon nanofibers by floating catalytic chemical vapor deposition according to claim 1, characterized in that: The following steps are involved: (1) Mixing the first catalyst component and the second catalyst component uniformly, and then vaporizing the catalyst and the promoter; The carbon source is vaporized at 70-500°C; Preheat the carrier gas to 100-600°C; (2) Synthesis of carbon nanofibers: The catalyst steam, the promoter steam, the carbon source steam and the preheated carrier gas are introduced into the synthesis furnace to synthesize small diameter nano-carbon fibers at 800-1400° C. The nano-carbon fiber powder is collected, the metal impurities in the prepared nano-carbon fiber powder are removed, and the powder is crushed to obtain the product.

3. The method according to claim 1, characterized in that: The accelerator is one or more of thiophene, mercaptan, sulfur powder, carbon disulfide, hydrogen sulfide and phosphoric acid.

4. The method according to claim 2, characterized in that: The carbon source is one or more of methane, ethylene, acetylene, ethanol, acetone, toluene, xylene, benzene and n-hexane.

5. The method according to claim 2, characterized in that: The carrier gas is one or more of hydrogen, nitrogen and argon.

6. The method according to claim 2, characterized in that In step (2), the catalyst vapor, promoter vapor, carbon source vapor, and preheated carrier gas are introduced into the synthesis furnace separately, or the catalyst vapor, promoter vapor, carbon source vapor, and preheated carrier gas are combined and introduced into the synthesis furnace; the flow rate of the carbon source, promoter, catalyst, and carrier gas mixture is 10 to 100 m / s, and the time in the synthesis furnace is 30 s to 10 min.

7. The method according to claim 2, characterized in that Water is added to the materials.

8. The method according to claim 2, characterized in that: Based on mass, the amount of catalyst used is 2-30% of the carbon source, the amount of promoter used is 10-50% of the catalyst used, and the amount of inhibitor used is 10-50% of the catalyst used.